2009
DOI: 10.1037/a0014280
|View full text |Cite
|
Sign up to set email alerts
|

The alarm call system of two species of black-and-white colobus monkeys (Colobus polykomos and Colobus guereza).

Abstract: Vervet monkey alarm calling has long been the paradigmatic example of how primates use vocalizations in response to predators. In vervets, there is a close and direct relationship between the production of distinct alarm vocalizations and the presence of distinct predator types. Recent fieldwork has however revealed the use of several additional alarm calling systems in primates. Here, the authors describe playback studies on the alarm call system of two colobine species, the King colobus (Colobus polykomos) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 64 publications
5
45
0
Order By: Relevance
“…These findings are consistent with the current theory of primate alarm calls, which states that aerial and terrestrial predators elicit acoustically distinct vocal behaviour (e.g., Seyfarth and Cheney 1980;Macedonia and Evans 1993;Zuberbühler 2000b;Digweed et al 2005;Fichtel et al 2005;Kirchhof and Hammerschmidt 2006;Schel et al 2009;Wheeler 2010). However, they are also at odds with N number of events per predator stimuli recorded and analysed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are consistent with the current theory of primate alarm calls, which states that aerial and terrestrial predators elicit acoustically distinct vocal behaviour (e.g., Seyfarth and Cheney 1980;Macedonia and Evans 1993;Zuberbühler 2000b;Digweed et al 2005;Fichtel et al 2005;Kirchhof and Hammerschmidt 2006;Schel et al 2009;Wheeler 2010). However, they are also at odds with N number of events per predator stimuli recorded and analysed.…”
Section: Discussionsupporting
confidence: 89%
“…Some species produce several acoustically distinct alarm calls in response to different predator types (Seyfarth et al 1980a, b;Manser et al 2002;Templeton et al 2005), but in others, the nature of the danger encountered is reflected by the number of calls per sequence (Schel et al 2009), the rate of call delivery (Lemasson et al 2010), the intensity of calls (Blumstein 1999), or by combinations of calls (Arnold and Zuberbühler 2006a, b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-urgency situations were when the presence of a predator was revealed by acoustic cues (playback of predator calls, alarm calls by Diana monkeys); high-urgency situations were when the predator was visible (predator models; real predator encounters). This distinction was based on the results of another experimental study with forest African primates, which showed that call intensity was higher when a predator was detected in the visual than the acoustic domain (57).…”
Section: Methodsmentioning
confidence: 99%
“…Inexperienced (i.e. without previous exposure) primates from several species recognize large-bodied felids, such as leopards (P. pardus), as inherently dangerous (Coss & Ramakrishnan, 2000;Davis, Parr, & Gouzoules, 2003;Schel, Tranquilli, & Zuberbühler, 2009) and children detect lions rapidly in computer displays (Penkunas & Coss, 2013a,b). As such, it is reasonable to predict that preschool children will perceive a lion as very dangerous.…”
Section: Experimental Questions and Hypothesesmentioning
confidence: 99%